Pengolahan dan Pengembangan Batang Talas Menjadi Olahan Keripik - Patria Susetya; Uswatun Hasanah; Nur Wahyuningsih; Ramlah Ramlah; Nur Asiah; Mahyarani Mahyarani; Linda Lestari; Ivon Prawita; Maysya Rizky Tri Juliana; Khafifah Ulumul Azri; Laila Hayati (Rengganis Jurnal Pengabdian Masyarakat, 2023)
Taro is one of a plant that can benefit most from bulbs, stems, and leaves. This community service activity aims to develop a talk-bar product that is one of the many rural businesses that diversify flavor and modify packaging and expand marketing. Developing the taro stems into chips will create new potential in Gegerung villages, as well as the use of internet media technology to promote promotional opportunities. This community service activity used a descriptive method to figure out matters in the territory to provide solutions to the problem. The target of this community service activity is one of the residents in North Orong Village who owns UMKM and is moving into the food fields. The study consists of three stages, namely observation, implementation and assistance, and product marketing. Observation activities and assistance to marketing products are going well and smoothly, starting with modifying packages to become more interesting, creating new flavors and then creating packaging logos, creating social media as an online medium of marketing, and then marketing them.